Police peer supporters in a domestic abuse-specific peer support initiative: Motivations, experiences and challenges - Ward, Rachel (International journal of police science & management, 2024)
Police peer support programmes traditionally focus on mental health issues and experiences of trauma in work. Increased awareness of domestic abuse (DA), its impacts in the workplace, and calls to adopt trauma-informed approaches in the emergency and public services in the UK have culminated in a southern English police force instituting a novel peer support programme for personnel who are experiencing DA. This qualitative study interviewed 16 self-selected DA peer supporters to explore their motivations and experiences in providing support for their colleagues and the application of trauma-informed practice. Findings support previous research on the ongoing prevalence of stigma around help-seeking in the police generally, and this is perhaps even more pronounced for DA. However, the presence of this form of peer support has symbolic value to challenge prevailing culture and foster increased confidence to make disclosures. Findings also indicate value in adopting DA-specific peer support from an organizational justice perspective because this may enable a greater sense of staff well-being. The approaches employed in the DA peer support programme exhibited implicit trauma-informed practice, which could be made more explicit and aligned to wider initiatives of creating a more trauma-informed police service.